On the presence and immunoregulatory functions of extracellular microRNAs in the trematode Fasciola hepatica. (February 2017) - Fromm, B.; Ovchinnikov, V.; Høye, E.; Bernal, D.; Hackenberg, M.; Marcilla, A.
Summary: Liver flukes represent a paraphyletic group of endoparasitic flatworms that significantly affect man either indirectly due to economic damage on livestock or directly as pathogens. A range of studies have focussed on how these macroscopic organisms can evade the immune system and live inside a hostile environment such as the mammalian liver and bile ducts. Recently, microRNAs, a class of short noncoding gene regulators, have been proposed as likely candidates to play roles in this scenario. MicroRNAs (miRNAs) are key players in development and pathogenicity and are highly conserved between metazoans: identical miRNAs can be found in flatworms and mammalians. Interestingly, miRNAs are enriched in extracellular vesicles (EVs) which are secreted by most cells. EVs constitute an important mode of parasite/host interaction, and recent data illustrate that miRNAs play a vital part. We have demonstrated the presence of miRNAs in the EVs of the trematode species Dicrocoelium dendriticum and Fasciola hepatica (Fhe) and identified potential immune‐regulatory miRNAs with targets in the host. After our initial identification of miRNAs expressed by F. hepatica, an assembled genome and additional miRNA data became available. This has enabled us to update the known complement of miRNAs in EVs and speculate on potential immune‐regulatory functions that we review here.